Knowledge and Awareness About Polycystic Ovarian Syndrome Among Libyan Females - Najwa Alaswad; Ayah Elmabrouk; Eshaima Abugdera (AlQalam Journal of Medical and Applied Sciences, 2024)
Polycystic Ovarian Syndrome (PCOS) has a major impact throughout life on the reproductive and metabolic health of the women worldwide. This study aimed to determine knowledge and awareness of PCOS among Libyan females. A cross-sectional design was adopted using self-administrative questionnaire to collect the data online on social media. Descriptive and inferential statistics were used for data analysis by SPSS. The study revealed 82 % of participated Libyan females had a good knowledge about PCOS and there is a significant association of knowledge of PCOS with the educational level of participants. The alarming concern is the low awareness of participants about long-term complications of PCOS especially about cardiovascular disease and diabetes mellitus, breast cancer, and uterine cancer. There was a good level of knowledge of PCOS among Libyan females but need to increase awareness about long-term complications such as hypertension, diabetes mellitus, uterine and breast cancer تؤثر متلازمة تكيس المبايض بشكل كبير على الصحة الإنجابية والأيضية للنساء في جميع أنحاء العالم طوال الحياة. تهدف هذه الدراسة إلى تحديد المعرفة والوعي بمتلازمة تكيس المبايض بين النساء الليبيات. تم اعتماد تصميم مقطعي باستخدام استبيان ذاتي الإدارة لجمع البيانات عبر الإنترنت على وسائل التواصل الاجتماعي. تم استخدام الإحصاءات الوصفية والاستدلالية لتحليل البيانات بواسطة برنامج SPSS. كشفت الدراسة أن 82٪ من النساء الليبيات المشاركات لديهن معرفة جيدة بمتلازمة تكيس المبايض وهناك ارتباط كبير بين معرفة متلازمة تكيس المبايض والمستوى التعليمي للمشاركات. والقلق المثير للقلق هو انخفاض وعي المشاركات بالمضاعفات طويلة المدى لمتلازمة تكيس المبايض وخاصة أمراض القلب والأوعية الدموية ومرض السكري وسرطان الثدي وسرطان الرحم. كان هناك مستوى جيد من المعرفة بمتلازمة تكيس المبايض بين النساء الليبيات ولكن هناك حاجة إلى زيادة الوعي بالمضاعفات طويلة المدى مثل ارتفاع ضغط الدم ومرض السكري وسرطان الرحم وسرطان الثدي